Dating the Composition of the First Bible? Hebrew Ostraca, Literacy in Israel/Judah, and the Bible - Kletter, Raz (Scandinavian journal of the Old Testament, 2025)
In several articles, a group of scholars (Faigenbaum-Golovin et al. 2016; 2020; 2021; Finkelstein 2016; Shaus et al. 2020) reached conclusions about the number of writers of the Hebrew ostraca from Arad and Samaria. Not content with this result, the group added far-fetched assertions. They claimed that the Arad ostraca show a high degree of literacy in Judah ca. 600 BCE, spreading far beyond “professional” scribes. Only this high degree, they argued, fits major compositions of biblical texts. They insisted that Hebrew scribal activity declined after 586 BCE to such an extent that no major composition of biblical texts was possible in Yehud and Samaria ca. 600-200 BCE. This article criticizes these sensational claims. It does not provide answers for the composition of the Bible.